Rancangan Penerangan Jalan Universitas Riau Menggunakan Software Dialux Evo - Liska Diana; Feranita Feranita; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Public road lighting facilities are needed to support the activities and mobility of road users. Factor affecting. the point of view of the right type of lamp, the pole distance, the boom length and boom angle of lamp. This is done so that road lighting can be implemented optimally, such as the use of energy-saving lamps and the design of road lighting designs in accordance with SNI. This research aims to evaluate and propose a PJU design by maximizing the efficiency of the lighting system. The study area used for research is the main road of Riau University, especially the main campus of UNRI which is in Panam Pekanbaru. To facilitate the design process, software for lighting simulation is used, namely DIALux evo 8.2. The results of the study refer to SNI 7391:2008. The lamps used 13,4 watts LED with 1600 lumens and 14,6 watts LED with 2200 lumens adapts to lighting needs on the road so as to minimize use of poles and lamps. Based on the results of calculations that have been carried out on the road lighting parameters of the University of Riau, the pole distance is obtained in the range of 10 meters - 17 meters adjusting the distribution of light on the road, the boom length in the range of 0,5 meter - 8.2 meters adjusting the distance of the pole to the road, the boom angle in the range of 0 ° - 15 ° adjusts to the position of the road to the lights, The average illumination level is in the range of 2,93 Lux – 4,38 Lux with an evenness of 0.42 - 0.6 and the glare threshold is in the range of 0 - 2 where the maximum glare threshold is 4. So with this analysis, it is able to produce efficient installation of road lighting and optimized according to SNI. Keywords: public road lighting, road lighting, LED, DIALux